Effect of Ultrasound Combined With Microbubble Therapy on Interstitial Fluid Pressure and VX2 Tumor Structure in Rabbit - Zhang, Qianyun; Jin, Hai; Chen, Liping; Chen, Qiaoli; He, Yan; Yang, Yuwen; Ma, Suihong; Xiao, Shuyi; Xi, Fen; Luo, Qiong; Liu, Jianhua (Frontiers in Pharmacology, 2019)
Interstitial fluid pressure (IFP) in tumor tissue is significantly higher than that in normal tissue, which reduces the effectiveness of therapeutic drugs. There are several methods to decrease the IFP, such as normalizing blood vessel, decreasing hyaluronic acid and collagen fiber content in the extracellular matrix (ECM), and recovering lymphatic function. Reducing tumor IFP might be developed as a novel approach in cancer therapy. In this study, we aimed to elucidate the relationship between ultrasound combined with microbubble therapy and IFP, and the associated mechanism. VX2 tumor in rabbit was treated with ultrasound combined with microbubbles at different intensities. The IFP was measured using the wick-in-needle (WIN) method. The collagen and reticular fibers were stained by Masson and Gordon–Sweets, respectively. The results showed that low-frequency non-focus ultrasound combined with microbubbles therapy influences the IFP in tumor tissues; low-frequency non-focus ultrasound with low pressure increased the IFP, whereas middle–high pressure decreased the IFP. The results showed that the structure and content of collagen and reticular fibers in tumor tissue were rarely influenced by the treatment. Our study provides a novel approach of reduced IFP antitumor therapy.